Early Christian Encounters with Town and Countryside : Essays on the Urban and Rural Worlds of Early Christianity - Tiwald, Markus (Novum Testamentum et Orbis Antiquus Studien zur Umwelt des Neuen Testaments, 2021)
Intro -- Title Page -- Copyright -- Body -- Markus Tiwald / Jürgen K. Zangenberg: "Early Christian Encounters with Town and Countryside" -- 1. Methodological Reflections -- 2. Jesus and the Early Jesus Movement -- 3. "Pauline Christianity" -- 4. Early Christian Environments from the First to the Second Century -- 5. Beyond Christianity -- 6. Acknowledgements -- "Town" and "Countryside" - Complement or Contrast? Methodological Reflections -- Frits Gerard Naerebout: ˋUrban' and ˋRural' in Early Christianity: Opposition or Complement? -- 1. Early Christianity: The Urban Hypothesis -- 2. Questioning the Urban Hypothesis: Demographics -- 3. Questioning the Urban-Rural Dichotomy -- 4. "Urban Religion": Does it Actually Exist? -- 5. The Urban-Rural Divide in Ancient Sources -- 6. Rural Christians in our Sources -- 7. Conclusions -- Bibliography -- Reinhard von Bendemann: Interrelations between Urbanity and Rurality -- 1. Man: A City-Building Animal? -- 2. Basic Perspectives of the History of Research -- 3. Historical Perspectives -- 4. The Complementarity of City/Town/Urbanity and Country‍(side)/Rurality and its Hermeneutic Relevance for the History and Literature of Early Christianity -- 4.1 The Complementarity of Town and Country‍(side): Consequences for the Reconstruction of the History of Early Christianity -- 4.2 The Dimension of Literary/Narrative Concepts of Early Christian Documents -- 5. Conclusion -- Bibliography -- Martin Ebner: Das frühe Christentum und die Stadt -- 1. Methodisch-hermeneutische Grundsatzfragen -- 1.1 Ein empirisches Faktum: Christliche Gemeinden in Städten des Imperium Romanum -- 1.2 Gattung „Stadt" und historische Veränderungen -- 1.3 Gottes Herrschaft im Imperium Romanum -- 1.4 Methodik und Vorgehen -- 2. Exemplarische Analysen -- 2.1 Römische Territorialstruktur und die Mental Map des Paulus.